Peran Pemerintah Daerah dalam Pengembangan Ekonomi Lokal Melalui Sektor Pertanian Agropolitan (Studi pada Badan Perencanaan Pembangunan Daerah (BAPPEDA) dan Dinas Pertanian dan Kehutanan Kota Batu) - Yunitasari, Anggun (Jurnal Administrasi Publik, 2013)
Abstract: The City Government's Role in Local Economic Development Through Agriculture Agropolitan (Case study of Badan Perencanaan Pembangunan Daerah (BAPPEDA) dan Dinas Pertanian dan Kehutanan Kota Batu ) Batu city is geographically has abundant natural resources. To be able to maximize the potential of agricultural resources , and the local Economic Development efforts , naturally the people of Batu has tried to optimize the use of natural resources through the Agropolitan program seed. Agropolitan concept is seen as a concept that can solve problems of rural-urban imbalance.In this case the role of local government was considered quite a role in supporting the local economy develpment Agropolitan the agricultural sector. However, lack of resources is one of the obstacles farmers today, so it needs to be improved as well as the role of government through education and formation of farmer groups so that farmers can work together to improve agricultural products in the region. This research is a naturalistic, qualitative - descriptive approach . Source of data used primary data and secondary data. This study concluded that local economic development through agriculture Agropolitan have some focal point in order to thrive, namely 1. Partnership or cooperation that exists in all levels of stakeholders, 2. Institutional Development of Farmers in the agricultural sector Agropolitan, 3. Collaboration of various sectors in Region Development Agropolitan encourage increased efficiency, productivity, control , and application of technologies by the public, 4. The economic growth in the region Agropolitan Development. Economic growth is the result of capital accumulation and investments made primarily by the private sector which can increase the productivity of the economy. Keywords : Local Economic Development, Agriculture Agropolitan Abstrak: Peran Pemerintah Daerah dalam Pengembangan Ekonomi Lokal melalui Sektor Pertanian Agropolitan (Studi pada Badan Perencenaan Pembangunan Daerah (BAPPEDA) dan Dinas Pertanian dan Kehutanan Pemerintah Kota Batu) Kota Batu secara geografis memiliki potensi sumberdaya alam yang berlimpah. Untuk dapat memaksimalkan potensi sumberdaya pertanian dalam upaya Pengembangan Ekonomi lokal, masyarakat Kota Batu telah berupaya melakukan optimalisasi pemanfaatan sumberdaya alam unggulan melalui Program Agropolitan. Konsep agropolitan dipandang sebagai konsep yang menjanjikan teratasinya permasalahan ketidakseimbangan perdesaan-perkotaan selama ini. Dalam hal ini peran pemerintah daerah sudah dirasa cukup berperan dalam mendukung pegembangan ekonomi lokal pada sektor pertanian agropolitan. Namun kurangnya sumber daya petani merupakan salah satu kendala saat ini, sehingga perlu terus ditingkatkan peran serta pemerintah melalui penyuluhan dan pembentukan kelompok tani agar para petani dapat bekerjasama dalam meningkatkan produk pertanian unggulan di daerahnya. Pengembangan ekonomi lokal melalui sektor pertanian agropolitan mempunyai beberapa titik fokus agar dapat berkembang, yakni 1.Kemitraan yang terjalin dalam semua tingkatan stakeholder, 2.Pengembangan Kelembagaan Petani sektor pertanian Agropolitan, 3.Kolaborasi yang mendorong peningkatan efisiensi, produktivitas, dan penerapan teknologi masyarakat, 4. Terjadinya pertumbuhan ekonomi yang dapat menaikkan produktivitas perekonomian. Kata Kunci: Pengembangan Ekonomi Lokal , Pertanian Agropolitan